Cytosolic aromatic aldehyde dehydrogenase provides benzoic acid for xanthone biosynthesis in Hypericum - Singh, Poonam (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.